Rancang Bangun Sistem Informasi Standar Operasional Prosedur (SOP) Berbasis Web Menggunakan Framework Laravel Pada Balai Penerapan Modernisasi Pertanian Jambi - Ahmad Fatchul Huda; Albet Triadi (LKP KARYA PRIMA KURSUS, 2026)
The advancement of information technology requires government institutions to implement administrative digitalization to improve effectiveness and transparency. The management of Standard Operating Procedures (SOP) at the Balai Penerapan Modernisasi Pertanian (BRMP) Jambi is still conducted manually and in a fragmented manner, resulting in difficulties in document retrieval, updating, distribution, and monitoring. This study aims to design and develop a web-based SOP Information System using the Laravel Framework. A descriptive qualitative approach was employed through observation, interviews, and literature review, while system development applied the Rapid Application Development (RAD) method. System testing was conducted using black box testing and feasibility evaluation through a Likert scale, indicating a very feasible user acceptance level. The system effectively supports administrative digitalization and enhances SOP management at BRMP Jambi.